2015
DOI: 10.1002/mds.26270
|View full text |Cite
|
Sign up to set email alerts
|

King's Parkinson's disease pain scale, the first scale for pain in PD: An international validation

Abstract: Pain is a key unmet need and a major aspect of non-motor symptoms of Parkinson's disease (PD). No specific validated scales exist to identify and grade the various types of pain in PD. We report an international, cross-sectional, open, multicenter, one-point-in-time evaluation with retest study of the first PD-specific pain scale, the King's PD Pain Scale. Its seven domains include 14 items, each item scored by severity (0-3) multiplied by frequency (0-4), resulting in a subscore of 0 to 12, with a total possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
185
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(210 citation statements)
references
References 37 publications
19
185
0
6
Order By: Relevance
“…The correlations between number of experienced types of pain and other variables in the study were low or moderate as a whole and lower than the correlations between severity of pains and those variables. 10 The only close association between number of different types of pain and other constructs in the study was observed with the PDQ-8 Index ( r S  = 0.55). Other studies have found relationships between pain and motor complications 13, 20 or disease progression, 21 but no with factors like age at diagnosis, disease duration, motor examination, or PD stage.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…The correlations between number of experienced types of pain and other variables in the study were low or moderate as a whole and lower than the correlations between severity of pains and those variables. 10 The only close association between number of different types of pain and other constructs in the study was observed with the PDQ-8 Index ( r S  = 0.55). Other studies have found relationships between pain and motor complications 13, 20 or disease progression, 21 but no with factors like age at diagnosis, disease duration, motor examination, or PD stage.…”
Section: Discussionmentioning
confidence: 64%
“…A ratio of patients to controls of 2:1 was estimated and 83 non-spousal, non-PD, age- and sex-matched controls were included. 10 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations